2022
DOI: 10.3390/antiox11050804
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Maintains Fruit Quality and Reduces Anthracnose in Postharvest Papaya via Enhancement of Antioxidants and Inhibition of Pathogen Development

Abstract: Papaya fruit is widely grown in tropical regions because of its sweet taste, vibrant color, and the huge number of health benefits it provides. Melatonin is an essential hormone that governs many plants′ biological processes. In the current study, the impact of melatonin on fruit ripening and deterioration in postharvest papaya fruit was explored. An optimum melatonin dose (400 μmol L−1, 2 h) was found to be effective in delaying fruit softening and reducing anthracnose incidence. Melatonin enhanced antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Previous studies have revealed that exogenous MT can enhance the AsA-GSH cycle by increasing AsA content, thereby maintaining the quality of guava fruit and enhancing its disease resistance [ 36 ]. Treatment with MT has been shown to increase the AsA content in papaya fruit and improve its quality [ 37 ]. Aghdam et al demonstrated that the application of MT effectively improved the levels of AsA and GSH in pomegranate fruit [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that exogenous MT can enhance the AsA-GSH cycle by increasing AsA content, thereby maintaining the quality of guava fruit and enhancing its disease resistance [ 36 ]. Treatment with MT has been shown to increase the AsA content in papaya fruit and improve its quality [ 37 ]. Aghdam et al demonstrated that the application of MT effectively improved the levels of AsA and GSH in pomegranate fruit [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results coincided with the findings of Qu et al [25], who reported that MLT induced the activities and related genes of defenserelated enzymes (POD, PAL, C4H, 4CL, and CAD), thus strengthening disease tolerance in postharvest blueberry fruit. In postharvest plum fruit [37] and papaya [34], MLT-induced increase in POD, PAL, C4H, and 4CL activities was found to be associated with reduced anthracnose and retention of fruit quality. As reviewed by Li et al [33] and Arnao and Hernández-Ruiz [15], MLT treatment induces phenylpropanoid metabolism in the fruits by elevating the activities and expressions of phenylpropanoid pathway-related enzymes (e.g., PAL and POD), which in turn improves resistance against pathogens.…”
Section: Discussionmentioning
confidence: 89%
“…The current study showed that exogenous MLT treatment reduced disease incidence and lesion expansion in goji fruit during postharvest storage. As a potential antifungal agent, exogenous MLT has been shown to play positive roles in combating pathogens and restricting the postharvest decay in grapes [33], blueberry fruit [25], papaya [34], cherry tomato [35], and apple fruit [36]. Exogenous MLT application to postharvest fruit enhances the content of endogenous MLT, which, in turn, regulates many physiological changes in the fruit, including quality changes, senescence deterioration, and stress tolerance [20].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro inhibition experiments were carried out with slight modifications following the methods described by Fan et al [40]. The ε-PL, SA, and MT were added to the PDA medium to give final concentrations of 0.125, 0.25, and 0.5 mg/mL of ε-PL, 0.4, 0.8, 1.2, and 1.6 mg/mL of SA, and 1, 2, 4, and 8 mg/mL of MT.…”
Section: Effects Of ε-Pl Sa and Mt Treatments On The Mycelial Growth ...mentioning
confidence: 99%